Robot selection in robotic intervention for ASD children - Ishak, Nor Izzati; Md Yusof, Hazlina; Sidek, Shahrul Na'im; Rusli, Nazreen (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper explains on the selection of a robot that is suitable for engagement with Autism Spectrum Disorder (ASD) children. Many robots were being developed to help these children to improve their behavior, communication skills, social interaction, joint attention and sensitivity. Recent researches done shown that a commercialize robot is better in early intervention therapy for the children because of its robustness and easily can be programmed by the parents and teachers. Instead, the physical appearance of the robot also plays an important feature for robot selection. Comparison studies were made between prototype robots that currently used in HumanRobot Interaction (HRI) and commercial robot. As a result, we proposed to have a commercial robot that is robust, simple, economical, durable and flexible to be changed to any desired form as our medium of interactions.